Pengaruh Model Problem Based Learning Berbantuan Media Pembelajaran Interaktif Canva untuk Meningkatkan Kemampuan Berpikir Kritis Fisika Peserta Didik - Khaliza, Siti Nur; Verawati, Ni Nyoman Sri Putu; Susilawati, Susilawati (Empiricism Journal, 2026)
This study aims to determine the effect of the problem-based learning model assisted by Canva interactive learning media to improve students' critical thinking skills in physics. The background of this study is based on the low critical thinking skills in physics due to the learning process that is still conventional and teacher-centered. The population in this study was all class XI MIPA SMAN 1 Wanasaba. Sampling was carried out using a purposive sampling technique, so that class XI MIPA 1 was obtained as the experimental class and class XI MIPA 2 as the control class. The type of research used was a quasi-experimental research design, namely nonequivalent control group design, where both samples will be given different treatments. The experimental class was given learning treatment using the problem-based learning model, while the control class was given treatment with conventional learning. The indicators of critical thinking skills measured were interpretation, analysis, evaluation, inference and explanation. The instrument used was a descriptive test of 9 questions. The average pretest score for the experimental class was 11.1 and the control class 13.5. Then the average value of the experimental posttest was 68.56 and the control 60.5. The critical thinking ability data was analyzed using parametric statistics, namely the t-test polled variance with a significance level of 5% and   obtained of 2.503 and  of  2.007. If  greater than , then Ho is rejected and Ha is accepted, so it can be concluded that the problem-based learning model assisted by Canva interactive learning media has an effect on students' critical thinking abilities in physics.